Pola Pergerakan dan Preferensi Wisata: Studi Kualitatif pada Wisatawan Gen Z Perempuan di Bandung - Safira Wahida Fajri Ikhwan; Darmaesti Darmaesti; Arinta Destri Larasati (Yayasan Literasi Sains Indonesia, 2025)
A significant number of Gen Z tourists, particularly females, visit Bandung from various regions and backgrounds, often unconsciously forming specific travel movement patterns. The aim of this study is to identify the types of tourist attractions, accommodations, and modes of transportation preferred by Gen Z tourists, as well as their travel movement patterns during their visit. Generation Z refers to individuals born between 1997 and 2012. While traveling, Gen Z tourists typically visit multiple destinations, which gradually form specific movement patterns. Travel movement patterns are defined as the shifts or transitions made by tourist from one attraction to another. This research uses a qualitative research method, with data collected through semi-structured interviews involving ten female Gen Z tourists aged between 18 and 27 years. The finding indicate that they are prefer natural attractions as their main tourism interest. In terms of accommodation, hotels are the most preferred option, particularly 2 star, 3 star, and 4 star categories. Regarding transportation, private cars and public transportation are the most frequently chosen modes of travel while visiting Bandung. Additionally, the research identified three types of movement patterns among Gen Z tourists, with the most common being the single point and base site patterns.